Implementasi Metode Diskusi Kelompok dalam Memperkuat Interaksi Belajar Siswa di Masa Digital pada Mata Pelajaran Pendidikan Agama Kristen di SMA Negeri 1 Kahayan Tengah - Elsa Oktavia (International Forum of Researchers and Lecturers, 2026)
This study is driven by the need to understand how students interact and learn in Christian Religious Education during the digital age. Group discussions are a good way to help students engage more in learning, work together, and talk with each other during lessons. However, some students still have low participation, don't feel confident sharing their thoughts, and are affected by digital technology, which can either help or make it harder to engage in learning. This study seeks to explain how the group discussion method is used, find out the different ways students interact during learning, and look at the things that help or stop this method from working well in Christian Religious Education at SMA Negeri 1 Kahayan Tengah. The study uses a qualitative method and focuses on a case study approach. Data were gathered by observing, talking to people, and keeping records with the principal, the Christian Religious Education teacher, the homeroom teacher, and the students. The results are likely to indicate that group discussions encourage students to engage actively, talk with each other, and work together while using digital tools. This study should help teachers and schools come up with good ways to teach students in the digital age.